The dissent papers : the voices of diplomats in the Cold War and beyond - Gurman, Hannah (Columbia University Press, 2012)
"Beginning with the Cold War and concluding with the 2003 invasion of Iraq, Hannah Gurman explores the overlooked opposition of U.S. diplomats to American foreign policy in the latter half of the twentieth century. During America's reign as a dominant world power, U.S. presidents and senior foreign policy officials largely ignored or rejected the reports, memos, and telegrams of their diplomats, especially when they challenged key policies regarding the Cold War, China, and wars in Vietnam and Iraq. The Dissent Papers recovers the invaluable perspective of these individuals and their commitment to the transformative power of diplomatic writing"--Provided by publisher.